Pelatihan Pendampingan Pembuatan Media Pembelajaran Interaktif dengan Memanfaatkan Aplikasi Zoom Meeting Basic Berbasis Multimedia Pada Guru YP TK Farhan An-Nur Batang Kuis-Deli Serdang - Suhendra Suhendra; Salam Irianto Nadeak; Komda Saharja (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
During the Covid-19 Pandemic, all levels of education starting from kindergarten to university began to use multimedia-based learning media, this was due to the lack of face-to-face learning at all levels of education. This Competitive Community Service Partner is a group of teachers from the Farhan An-Nur Kindergarten Islamic Education Foundation which is located on Jl. Peringgan Hamlet III, Tumpatan Nibung Village, Batang Kuis Subdistrict, Deli Serdang Regency. This Playgroup (KOBER) has 5 teachers and 52 students. During the Pandemic, schools run teaching and learning activities face to face and alternately, this is because the problem faced by partners is that teachers do not have the ability to create and design interactive multimedia-based learning media by utilizing conference apps, including basic zoom meetings. However, the quality of student learning continues to decline due to the short duration of study. The solutions offered are providing training in designing teaching materials, providing training in making learning videos by utilizing applications that are currently often used by teachers in conducting online learning, namely zoom meeting basic. The method is carried out by means of lectures and practices, with each type of training carried out 4x2 hours of meetings for 1 month. Monitoring and post implementation of competitive community service activities are carried out twice, namely the 1st month and 4th month after the program is completed to ensure the sustainability of the program that has been implemented